"Союз козаків-націоналістів” в Болгарії: консолідація козацького руху в документах 1930-х років - Громович, У. (Чорноморська минувшина, 2022)
До уваги читачів пропонуються документи про Козацьке культурно-освітнє і доброчинне братство «Союз козаків-націоналістів в Болгарії», що містять інформацію про діяльність, ідеї та лідерів товариства. За допомогою документів визначено орієнтовну дату заснування та основні завдання товариства. З’ясовано, що товариство мало Статут, активно брало участь у заходах української діаспори в Болгарії, взаємодіяло з урядом та іншими організаціями. The readers are offered documents about the Cossack cultural, educational and charitable brotherhood "Union of Cossack Nationalists in Bulgaria". During the specified period, the Cossacks experienced a difficult period of restoration, elevation and transformations. In the conditions of large-scale revolutionary movements and the armed struggle for Ukrainian statehood, attempts to consolidate Ukrainian emigration and the use of individual Ukrainian military-Cossack traditions in their activities played a rather noticeable role. During this time, the Ukrainian emigration created many Cossack centers abroad, which were engaged in popularizing the ideas of the Cossacks, the history of Ukraine in emigration, and sought the restoration of independent Ukraine. Today, this experience of the Cossack movement in the 1930s remains little-known for today, is little covered in literature and is available only in archives. Therefore, the found documents are valuable because they contain information about the activities, ideas and leaders of the Union of Cossack Nationalists in Bulgaria. With the help of documents, the article for the first time determined the approximate date of foundation and traced the main tasks of the society. The article found that the society had a charter that regulated its activities, participated in events of the Ukrainian diaspora in Bulgaria, interacted with the government and other organizations.